First record of the boneti-group of Coecobrya Yosii, 1956 (Collembola: Entomobryidae) from Thailand, with the description of three new cave species of the genus - Nilsai, Areeruk; Zeppelini, Douglas; Bellini, Bruno C.; Lima, Estevam C. A.; Jantarit, Sopark (Zootaxa, 2022)
Thailand holds one of the most diverse faunas of the genus Coecobrya Yosii, 1956, with 22 species reported from the country so far. In this study three new species of Coecobrya are described from subterranean environments: C. satasookae sp. nov. from Chaiyaphum province, C. cavicola sp. nov. from Phrae province and C. chompon sp. nov. from Ratchaburi province. The first two species belong to the tenebricosa-group, as they lack eyes, while C. chompon sp. nov. has 1+1 eyes and fits the boneti-group. Coecobrya satasookae sp. nov. and C. cavicola sp. nov. can be distinguished from each other and its congeners by the combination of antennal length, clypeal, dorsal head and thoracic chaetotaxy, whereas C. chompon sp. nov. is most similar to C. boneti (Denis, 1948) from Vietnam. However, it differs from the latter taxa mostly by the proportion of the antennae, ventral and dorsal head, thoracic, fourth abdominal chaetotaxy, plus the shape of the tenent hairs. C. chompon sp. nov. is the first record and description of a Coecobrya species from the boneti-group in Thailand. We also discuss the ecological niches of troglomorphic Coecobrya species in Thailand and the status of the boneti-group.